Community assembly of bacteria and archaea in coastal waters governed by contrasting mechanisms: A seasonal perspective. Issue 19 (15th September 2020) - Wang, Kai; Yan, Huizhen; Peng, Xin; Hu, Hanjing; Zhang, Huajun; Hou, Dandi; Chen, Wei; Qian, Peng; Liu, Junfeng; Cai, Jingbo; Chai, Xueliang; Zhang, Demin
Abstract: Marine planktonic bacteria and archaea commonly exhibit pronounced seasonal succession in community composition. But the existence of seasonality in their assembly processes and between‐domain differences in underlying mechanism are largely unassessed. Using a high‐coverage sampling strategy (including single sample for each station during four cruises in different seasons), 16S rRNA gene sequencing, and null models, we investigated seasonal patterns in the processes governing spatial turnover of bacteria and archaea in surface coastal waters across a sampling grid over ~300 km in the East China Sea. We found that archaea only bloomed in prokaryotic communities during autumn and winter cruises. Seasonality mostly overwhelmed spatial variability in the compositions of both domains. Bacterial and archaeal communities were dominantly governed by deterministic and stochastic assembly processes, respectively, in autumn cruise, probably due to the differences in niche breadths (bacteria < archaea) and relative abundance (bacteria > archaea). Stochasticity dominated assembly mechanisms of both domains but was driven by distinct processes in winter cruise. Determinism‐dominated assembly mechanisms of bacteria rebounded in spring and summer cruises, reflecting seasonal variability in bacterial community assembly. This could be attributed to seasonal changes in bacterial niche breadths and habitat heterogeneity across the study area. There were seasonal changes in environmental factors mediating the determinism‐stochasticity balance of bacterial community assembly, holding a probability of the existence of unmeasured mediators. Our results suggest contrasting assembly mechanisms of bacteria and archaea in terms of determinism‐vs.‐stochasticity pattern and its seasonality, highlighting the importance of seasonal perspective on microbial community assembly in marine ecosystems.